A structural investigation of the sulphated polysaccharides of Aeodes orbitosa and Phyllymenia cornea - Parolis, Haralambos (Rhodes University, Faculty of Science, Department of Chemistry, 1968)
A highly sulphated, methylated polysaccharide, aeodan, isolated from the red seaweed Aeodes orbitosa was shown to contain galactose, 2-̲̲O-methyl-D-galactose, 4-O̲-methyl-Lgalactose, 6-O̲-methyl-D-galactose, xylose, and glycerol. The polysaccharide was desulphated with methanolic hydrogen chloride. Periodate oxidation of aeodan and desulphated aeodan, followed by reduction and hydrolysis, revealed the presence of 1,4- and 1,3-linked galactose residues and 1,3-linked 6-O̲-methy l-D-galactose residues in aeodan. Treatment of aeodan with sodium hydroxide revealed that the majority of the ester sulphate groups were alkali stable. Methylation of desulphated aeodan revealed that the polysaccharide was composed entirely of 1,3 and 1,4 links. Methylation of aeodan revealed the presence of 1,3- and 1,4- linked units, 1,3-linked galactose-2-sulphate, and 1,3-linked galactose-2, 6-disulphate units in the polysaccharide. Partial hydrolysis of aeodan resulted in the isolation and characterisation of 3-O̲-D-galactopyranosyl-D-galactose and 4-O̲-ß-D-galactopyranosyl- D-galactose. A sulphated, methylated polysaccharide, phyllymenan, isolated from the red seaweed Phyllymenia cornea was shown to contain galactose, 2-O̲-methyl-D-galactose, 4-O̲-methyl L- galactose , 6-O̲-methyl -D-galactose, and xylose. The polysaccharide was completely desulphated with methanolic hydrogen chloride. Periodate oxidation of phyllymenan before and after desulphation revealed that removal of the sulphate ester groups had not produced any new adjacent hydroxyl groups. Alkali treatment of phyllymenan revealed that the ester sulphate groups were alkali stable. Methylation studies on phyllymenan revealed the presence of 1,3- and 1,4-linked units, 1,3-linked galactose-2-sulphate, and 1,3-linked galactose- 2,6-disulphate units in the polysaccharide. Partial hydrolysis of phyllymenan revealed the presence or 4-O-̲ß- D-Dgalactopyranosyl- D-galactosc, 4-O-̲ß-D-galactopyranosyl -2-0- methyl-D-galactose, a galactosylgalactose composed of D and L-galactose, and adjacent 6-O̲-methyl- and 2-O̲-methyl-D- galactose units in the polysaccharide.
Keywords: Polysaccharides; Marine algae -- Composition